KEJADIAN GASTROESOPHAGEAL REFLUX DISEASE (GERD) BERDASARKAN SKOR GERD-Q PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA TAHUN 2023 - Nurul Fadila Rahmadani Maradjabessy; Indrawanti Kusadhiani; Juen Carla Warella (PAMERI, 2023)
Gastroesophageal Reflux Disease (GERD) is a pathological condition due to backflow from the stomach into the esophagus, causing symptoms such as heartburn and regurgitation. Risk factors for GERD are mostly related to a person's lifestyle such as obesity, diet, smoking and stress. One group of individuals who have a high risk is students of the Faculty of Medicine in terms of a series of study loads that make students unable to maintain a good lifestyle. The purpose of this study was to determine the incidence and characteristics of Pattimura University Faculty of Medicine students who experience GERD based on the GERD-Q score. This research is a quantitative research with categorical descriptive study using cross sectional approach. The results showed that the prevalence of GERD was 40 people (15.2%) out of a total of 264 respondents. The majority were female 31 people (11.7%). The highest age was 18 years old, 16 people (6.1%). The most common symptom of GERD is regurgitation as many as 40 people (8.5%). The highest BMI in the normal group was 16 people (6.1%). The conclusion of this study showed that the prevalence of GERD in students of the Faculty of Medicine, Pattimura University was 40 people with the main complaint of regurgitation and the characteristics of respondents with GERD were mostly at the age of 18 years, female, and normal BMI group.